Fish Assemblages in Subtidal Seagrass Meadows Surrounding the West Sand, South China Sea - Ren, Qing-qiang; Leung, Priscilla T. Y.; Xu, Qing; Yan, Meng; Yang, Guo-han; Wei, Jie-hong; Liu, Min (Frontiers in Environmental Science, 2022)
Both beach seine (BS) and line transect-based underwater visual census (UVC) methods were applied to investigate fish assemblages of the West Sand (Xisha Islands, the South China Sea) seagrass meadows and its relationship with seagrass coverage. The West Sand seagrass meadows were divided into four survey areas, two (areas A and B) to the north and two (areas C and D) to the south. The average seagrass coverages (%) in the north were significantly higher than those in the south (p < 0.05). The dominant seagrass species is Thalassia hemprichii, contributing to over 70% substrate coverage in all four areas. A total of 843 individuals from 25 fish species belonging to 22 genera, 11 families and ten orders were recorded, with five species obtained by both BS and UVC methods. The labrids Halichoeres trimaculatus and Stethojulis strigiventer were the only two species dominated (the index of relative importance IRI > 500) in both BS and UVC methods. Fish assemblages among the four areas were significantly different (BS, p = 0.002; UVC, p = 0.002); area A was significantly different from areas B-D (p < 0.05) that mainly driven by the variation in H. trimaculatus density. Furthermore, fish assemblages of the four areas (abundance data) revealed by both BS (r2 = 0.8455) and UVC (r2 = 0.9354) methods showed high correlation to the seagrass coverage. The majority of the individuals (> 93%) recorded by BS and UVC methods were less than the total length at maturity (TLm), with 80.36% and 46.13% of individuals less than half sizes of their TLm, respectively. Our results, for the first time, approved the importance of seagrass meadows at the West Sand as fish nursery grounds. The ecological roles of seagrass habitats in South China Sea merit further investigation.